Effects of phosphatidylserine on mental states in elite shooters - Lu, J.; An, Y. (Exercise Biochemistry Review, 2018)
Objective The purpose of this study was to examine effects of a short-term oral supplementation of PS on biochemical stress indicators, whole brain neurotransmitters, mood states, and sleep quality in elite shooters.